Microbially available phosphorus in boreal forests: effects of aluminum and iron accumulation in the humus layer - Giesler, R.; Satoh, F.; Ilstedt, Ulrik; Nordgren, A. (2004)
Soil microorganisms play an important role in the mobilization of phosphorus (P), and these activities may be beneficial for plant P utilization. We investigated the effects on microbial P availability of different combinations of aluminum and iron (Al + Fe) concentrations and different P pools in humus soils from boreal forest ecosystems. We measured respiration rates in laboratory incubations before and after additions of glucose plus (NH4)2SO4 (Glu+N), with or without a small dose of KH2PO4. Glu+N was added in excess so that the availability of the inherent soil P would be growth-limiting for the microorganisms. The exponential increases observed in microbial growth after substrate additions (Glu+N) was slower for humus soils with high Al+Fe concentrations than for humus soils with low Al+Fe concentrations. Adding a small dose of KH2PO4 to humus soils with high Al+Fe concentrations did, however, increase the exponential growth, measured as the slope of the log-transformed respiration rates, by more than 200%. By contrast, the average increase in exponential growth was only 6% in humus soils with low Al+Fe concentrations. Almost eight times more carbon dioxide (CO2) was evolved between the substrate additions and the point at which the respiration rate reached 1 mg CO2 h–1 for soils with high Al+Fe concentrations compared to humus soils with low Al+Fe concentrations. The amount of CO2 evolved was positively related to the Al+Fe concentration of the humus soils (r 2 = 0.86, P < 0.001), whereas the slope was negatively related to Al+Fe concentration (r 2 = 0.70, P < 0.001). Easily available P forms were negatively related to the Al+Fe concentration, whereas organic P showed a strong positive relationship to Al+Fe (r 2 = 0.85, P < 0.001), suggesting that other forms of P, as well as inorganic P, are affected by the increased sorption capacity. The results indicate that P mobilization by microorganisms is affected by the presence of sorption sites in the humus layer, and that this capacity for sorption may relate not only to phosphate but also to organic P compounds.